A kinetic view of statistical physics - Krapivsky, Pavel L.; Redner, Sidney, 1951-; Ben-Naim, E. (Eli) (Cambridge ; New York : Cambridge University Press, 2010)
"Aimed at graduate students, this book explores some of the core phenomena in non-equilibrium statistical physics. It focuses on the development and application of theoretical methods to help students develop their problem-solving skills. The book begins with microscopic transport processes: diffusion, collision-driven phenomena, and exclusion. It then presents the kinetics of aggregation, fragmentation and adsorption, where the basic phenomenology and solution techniques are emphasized. The following chapters cover kinetic spin systems, both from a discrete and a continuum perspective, the role of disorder in non-equilibrium processes, hysteresis from the non-equilibrium perspective, the kinetics of chemical reactions, and the properties of complex networks. The book contains 200 exercises to test students' understanding of the subject. A link to a website hosted by the authors, containing supplementary material including solutions to some of the exercises, can be found at www.cambridge.org/9780521851039"--Provided by publisher.
Aperitifs -- Diffusion -- Collisions -- Exclusion -- Aggregation -- Fragmentation -- Adsorption -- Spin dynamics -- Coarsening -- Disorder -- Hysteresis -- Population dynamics -- Diffusive reactions -- Complex networks.
Includes bibliographical references (p. [471]-482) and index.
Keywords: Nonequilibrium statistical mechanics; Statistical physics